Research Trends in Eggplant (Solanum melongena L.) Breeding: A Bibliometric Study - Samsul Ma’arif; Asifa Asifa; Iskandar Iskandar (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Eggplant (Solanum melongena L.) is an important horticultural crop with high economic and nutritional value. Climate change, environmental stress, and food security concerns have accelerated research on eggplant breeding worldwide.. However, comprehensive evaluations of research trends in eggplant breeding remain limited. Therefore, this study aimed to perform a bibliometric analysis of global eggplant breeding research published between 2016 and 2026. Data were collected from the Scopus database using the query Title-Abs-Key ((“eggplant” or “aubergine”) and (“plant breeding” or hybridization or cultivar or “hybrid variety”)). The analysis included English-language articles and was conducted using Bibliometrix/Biblioshiny and VOSviewer. A total of 562 documents were analyzed. The results showed that scientific publications increased substantially after 2019, indicating growing global interest in eggplant genetic improvement. China was the most productive country, with 117 publications and 2,124 citations, followed by the United States (35 publications), Spain (35 publications), and India (15 publications). Collaboration analysis demonstrated extensive international partnerships, whereas keyword and thematic analyses revealed dominant topics related to hybridization, disease resistance, stress tolerance, antioxidants, and molecular breeding. Recent studies have increasingly focused on abiotic stress, heterosis, and nutritional quality improvement. This study provides insights into research development and emerging trends in eggplant breeding research.